2021
DOI: 10.5194/hess-2021-42
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Satellite rainfall products outperform ground observations for landslide forecasting in India

Abstract: Abstract. Landslides are among the most dangerous natural hazards, particularly in developing countries where ground observations for operative early warning systems are lacking. In these areas, remote sensing can represent an important tool to forecast landslide occurrence in space and time, particularly satellite rainfall products that have improved in terms of accuracy and resolution in recent times. Surprisingly, only a few studies have investigated the capability and effectiveness of these products in lan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, GSMaP-GNRT outperformed CMORPH-CRT in discriminating the occurrence/non-occurrence of landslide-triggering rainfall events. Brunetti et al (2021) showed that satellite-derived rainfall products outperformed ground observations for landslide prediction in India. However, their ground observation dataset has a coarser spatiotemporal resolution compared to satellite-derived rainfall products.…”
Section: Discussionmentioning
confidence: 99%
“…However, GSMaP-GNRT outperformed CMORPH-CRT in discriminating the occurrence/non-occurrence of landslide-triggering rainfall events. Brunetti et al (2021) showed that satellite-derived rainfall products outperformed ground observations for landslide prediction in India. However, their ground observation dataset has a coarser spatiotemporal resolution compared to satellite-derived rainfall products.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Papua New Guinea used TRMM satellite precipitation estimates (Robbins, 2016). Brunetti et al (2021) showed that rainfall thresholds estimated from satellite products outperformed those derived from ground observations in India. Even Indonesia tested similar data to support its landslide EWS.…”
Section: Introductionmentioning
confidence: 99%